Methods of adaptability and stability applied to eucalyptus breeding - Santos, Osmarino Pires dos; Carvalho, Ivan Ricardo; Nardino, Maicon; Olivoto, Tiago; Pelegrin, Alan Junior de; Szareski, Vinícius Jardel; Ferrari, Mauricio; Nunes, Andrei Caíque Pires; Demari, Gustavo Henrique; Lautenchleger, Francine; et al. (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the consistency of the methods of Annicchiarico, Lin & Binns, Wricke, and factor analysis in identifying eucalyptus clones with stability, adaptability, and high productive potential. Eight‑four clones, with three years of age, from the genetic breeding program of the company CMPC Celulose Riograndense were used. Three field experiments were carried out in a randomized complete block design, in an 84x3 factorial arragement, with 20 replicates of one plant per plot. The clones were evaluated as to diameter at breast height, plant height, and volume of wood. The methods of Annicchiarico and Lin & Binns are highly correlated with each other, and their use together with the method of Wricke is a sound strategy for the evaluation of eucalyptus clones. The factor analysis identified broadly adaptable clones, and some of them were the same ones identified by the methods of Annicchiarico and Lin & Binns. The use of the mean classification of the clones, along with the factor analysis, is efficient to identify the most adapted, stable, and productive ones among a high number of genotypes.